2022
DOI: 10.1021/acs.jmedchem.2c00308
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the First Highly Selective and Broadly Effective Macrocycle-Based Type II TRK Inhibitors that Overcome Clinically Acquired Resistance

Abstract: Tropomyosin receptor kinase (TRK) secondary mutations mediating acquired resistance, especially at the solvent-front (SF) and the DFG motif, represent an unmet clinical need. Small-molecule macrocyclic kinase inhibitors have displayed significant advantages in overcoming clinical resistance driven by kinase mutations; however, all reported small-molecule macrocyclic TRK inhibitors are all type I inhibitors and are therefore much more sensitive to SF than xDFG mutations. Novel therapeutics for patients with xDF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Molecular modeling studies indicated 8b bound to the adenosine 5′-triphosphate (ATP)binding pocket of TRKA G595R in a type II binding mode similar to that of 8. 20 Particularly, the methylated amide macrocyclic linker fitted nicely in the ATP binding pocket away from Gly595 with a distance of 5.7 Å, which suggested less steric clash with Arg595 than that of 8. Based on the predicted model, we noticed that the restricted methylated amide points to Glu518 at the ploop without direct interactions.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Molecular modeling studies indicated 8b bound to the adenosine 5′-triphosphate (ATP)binding pocket of TRKA G595R in a type II binding mode similar to that of 8. 20 Particularly, the methylated amide macrocyclic linker fitted nicely in the ATP binding pocket away from Gly595 with a distance of 5.7 Å, which suggested less steric clash with Arg595 than that of 8. Based on the predicted model, we noticed that the restricted methylated amide points to Glu518 at the ploop without direct interactions.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…In our previous study, we have reported a highly selective macrocycle-based potent type II TRK inhibitor 8 (Figure ), which displayed digital nanomolar activity against various DFG mutations but moderate activity against SF (TRKA G595R ) and GK (TRKA F589L ) mutants with IC 50 values of 493.7 nM and 2.1 μM, respectively . The predicted binding modes of 8 with TRKA G595R showed that the smaller-sized methylethanediamine group may still exist as a steric hindrance with the mutant Arg595 (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclization is an effective strategy to develop novel lead compounds by increasing structural novelty, expanding scaffold diversity and taming complexity. Lin et al at Prelude Therapeutics initiated a project to discover potent and selective PRMT5 inhibitors employing this cyclization strategy. The conformation of compound 1 was initially restricted via a five-membered ether in their new inhibitor design, as exemplified by compound 2 (Figure ).…”
Section: Prmt5 Inhibitorsmentioning
confidence: 99%
“…Previously discovered Larotrectinib (LOXO-101), Entrectinib (RXDX-101), compounds 7b and 8 for NTRK-fusion tumors are pan-TRK inhibitors without subtype selectivity ( Supporting Information Fig. S1A ), causing a series of side effects 2 , 3 , 4 . So far, there have been no reports of TRKA selective inhibitors for clinical anti-tumor therapy or clinical trials, and no related studies have been published.…”
mentioning
confidence: 99%